STRATEGI PENGEMBANGAN AGRIBISNIS DI KAWASAN AGROPOLITAN KABUPATEN GARUT - Febrianti, Tintin; Irianti, Efita Fitri (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Agribusiness development through agropolitan is one way to achieve development evenly in rural areas. Garut Regency as an agrarian region through regional planning has determined several sub-districts as an agropolitan area. The districts referred to are Cikajang, Bayongbong, Cigedug, Cisurupan, Sukaresmi and Pasirwangi Districts. This research conducted to determine the development strategy of several superior agribusiness commodities originating from each of these sub-districts. The data obtained analyzed using the SWOT method to identify internal and external factors including: Strength, Weakness, Opportunity, Threat and then determined by each strategy formulation.